Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3389/fnhum.2014.00077
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised learning of facial emotion decoding skills

Abstract: Research on the mechanisms underlying human facial emotion recognition has long focussed on genetically determined neural algorithms and often neglected the question of how these algorithms might be tuned by social learning. Here we show that facial emotion decoding skills can be significantly and sustainably improved by practice without an external teaching signal. Participants saw video clips of dynamic facial expressions of five different women and were asked to decide which of four possible emotions (anger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…The SBIP + IMP appears to be more effective than the SBIP condition in addressing the emotion-decoding abilities of IPV perpetrators, thus supporting the second hypothesis. A previous study found that adults' facial emotion-decoding skills are not completely innate and can be significantly improved through learning (Huelle, Sack, Broer, Komlewa, & Anders, 2014). Our data reinforced this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The SBIP + IMP appears to be more effective than the SBIP condition in addressing the emotion-decoding abilities of IPV perpetrators, thus supporting the second hypothesis. A previous study found that adults' facial emotion-decoding skills are not completely innate and can be significantly improved through learning (Huelle, Sack, Broer, Komlewa, & Anders, 2014). Our data reinforced this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study found that adults’ facial emotion‐decoding skills are not completely innate and can be significantly improved through learning (Huelle, Sack, Broer, Komlewa, & Anders, ). Our data reinforced this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The study confirms the findings of an earlier study in which the ability to accurately assess emotions through decoding facial expression was enhanced through learning 4. The increase in cognitive empathy (the ability to adopt another’s perspective) was likely influenced by the cognitive flexibility generated by problem-solving strategies taught in SBIP 5.…”
Section: Commentarysupporting
confidence: 87%
“…These results offer a target for future interventions in designing intervention packages that focus on reinforcing treatment adherence in the first stages of the intervention. Additionally, several studies have demonstrated that emotion decoding and cognitive flexibility have improved through training in several non-violent populations [44,45,46] and in IPVAW perpetrators [20,21,22,23,24,25,26,27,28,29,30].…”
Section: Discussionmentioning
confidence: 99%